2013
DOI: 10.1007/s11547-013-0968-1
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation of liver metastases to overcome the limitations of radiofrequency ablation

Abstract: Percutaneous MWA of liver metastases >3 cm or located near vessels (>3 mm) can be considered a valid and safe option, probably preferable to RFA. Further studies are required to confirm these encouraging initial results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 30 publications
1
38
0
2
Order By: Relevance
“…The morbidity in these studies has ranged from 0 to 60 % and mortality 0-2 % [6,[19][20][21]. The current study, with no morbidity or mortality via a predominantly laparoscopic approach, compares favorably with these reports.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The morbidity in these studies has ranged from 0 to 60 % and mortality 0-2 % [6,[19][20][21]. The current study, with no morbidity or mortality via a predominantly laparoscopic approach, compares favorably with these reports.…”
Section: Discussionsupporting
confidence: 52%
“…In the literature, different authors have reported on open [7,[16][17][18], percutaneous [6,19] and laparoscopic [20,21] applications of MWA for various malignant liver tumors. The morbidity in these studies has ranged from 0 to 60 % and mortality 0-2 % [6,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Length and width of the ablation as well as CT density within the ablation zone were recorded. H&E was used only to assess evidence of inflammation within the margins [18]. TUNEL is a common method for detecting DNA fragmentation, and can definitively identify non-viable cells at 24 hours [19].…”
Section: Methodsmentioning
confidence: 99%
“…Surgical treatment remains the treatment of choice for the curative therapy of liver malignancies; however, a considerable number of patients are inoperable [2,3]; consequently, alternative treatments, such as radiofrequency ablation (RFA) [4], microwave ablation (MWA) [5,6], laserinduced-thermotherapy (LITT) [7], cryoablation [8], transarterial chemoembolization (TACE) and stereotactic radiotherapy, have advanced over the last decade. MWA has been shown to combine the benefits of RFA while having its own benefits, namely, higher ablation volumes, shortened treatment duration, possibility of multiple antenna use, reduced susceptibility to the heat-sink effect and higher rates of local tumour control [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%